Consequences of receptor editing at the λ locus: Multireactivity and light chain secretion - Doyle, Colleen M. (National Academy of Sciences, 2006)
To investigate the manner in which B cells with λ light (L) chains undergo receptor editing, we have studied hybridoma panels from 56R/κ-deleted (kdel) mice. 56R/kdel mice only produce four L chains (λ1, λ2, λ3, and λX). They also have a simplified heavy (H) chain repertoire: All B cells start out with a 56R anti-DNA H chain. A few frankly autoreactive 56R λ1 cells appear to escape into the periphery, but the majority of the peripheral B cell repertoire in 56R/kdel is made up of B cells expressing the 56R H chain with the λX L chain. Surprisingly, 56R λX B cells are multireactive, binding to a variety of self and nonself antigens, including dsDNA (albeit at reduced affinity compared with the other λ L chains). Another significant population in the 56R/kdel mouse consists of allelically included B cells that express λX along with another L chain. The multireactivity of both 56R λX and 56R λX/λ1 receptors could contribute to autoimmunity if these B cells were to become activated. Also found among 56R/kdel hybridomas are clones that have inactivated the H chain and secrete only L chains. These clones may represent products of exhaustive rearrangement. Multireactivity, allelic inclusion, and L chain secretion are three consequences of editing at the λ locus that may predispose toward the development of autoimmunity.